Konsep sastera Islam oleh Kassim Ahmad (the concept of Islamic literature by Kassim Ahmad) - Yaacob, Adli (Global Academic Excellence, 2019)
The study revolves around the concept of Islamic Literature as proposed by Kassim Ahmad in his refutation against the view of Shanon Ahmad in a debate that took place in a number of issues of the local Literature Magazine “Dewan Sastera”. It was observed that form his arguments that Kassim adopted a liberal stand especially interpreting some of the verses of the Quran, on which he built his argument to conceptualize the concept of Islamic Literature. It must be admitted however that the debate had revealed Kassim’s writing rigor when defending his views. The debate had reopened the interest in the topic among the academia and the literary circle although the topic itself had been discussed by others before inviting fresh views from some of them. Indeed, the debate had managed to spark new interest in the topic as it was coincidentally take place during the era of which the government was keen in implementing the internalization of Islamic values policy and against the backdrop of the success of the Islamic revolution in Iran. Since the Islamization project had begun to gain momentum in some areas such as economy, politic, administration etc., the same question was asked whether Islamization is applicable in the realm of literature as well. This paper attempts to consider this question.